Educators’ attitudes toward artificial intelligence in higher education: a systematic review of influencing factors and hr implications - Yulianto, Yulianto; Junaidi, Junaidi; Saryono, Udin (Institute of Computer Science (IOCS), 2025)
This systematic review examines educators' attitudes toward AI in higher education, analyzing adoption drivers, ethical concerns, and institutional support. Using PRISMA guidelines, we analyzed 26 studies (2018-2024) from Scopus and Google Scholar, categorizing findings into cognitive (knowledge), affective (ethical worries), and contextual (support) dimensions. Results show educators' AI acceptance depends on their technical understanding, ethical considerations, and institutional backing. While AI boosts productivity through automation, concerns about dehumanization and bias create resistance, with adoption varying by digital literacy and regional policies. We propose a model positioning educators as key stakeholders in AI integration. Practical recommendations include hands-on training, ethical guidelines, and inclusive decision-making to balance technological progress with human needs for sustainable implementation. The study highlights the need to address both technical and human factors in AI adoption.